José María Arguedas: Pluricultural Peru, a real and imaginary world - Aranda Dioses, Edith (2011)
With regard to the narrative and intellectual production of José María Arguedas we try in this article to outline some ideas around the following question: How does the world imagined by Arguedas as a narrator provide us with a knowledge of the real world of what our country is? We find in his work intersections of literary fiction with the social sciences, there being a certain complementarity between these two ways of approaching social life, taking into account that both the novel and the science of society are modern forms that attempt to present a total reality that no one can encompass. From two different but not exclusive points of view, Arguedas brings us closer to the knowledge and valuation of the Andean world from an option that bets for the recognition of the Andean culture as one of the foundations of our identity.